Defending the Vatican: The Palatine Guard and the German Occupation of Rome in World War II - David Alvarez (Nuova Antologia Militare)
The few accounts of the pope’s Palatine Guard in World War II uncritically extol the performance of this obscure military unit, emphasizing the loyalty and commitment of its members and applauding its service during the German occupation of Rome. The wartime records of the Guard, newly available at the Archivio Apostolico Vaticano, allow a more nuanced and comprehensive appraisal. These records reveal a purely ceremonial unit struggling, not always successfully, to transform into an operational military force whose performance in the face of the German threat to Vatican City was constrained by deficiencies in discipline, training, and equipment.